ANALISIS PENDAPATAN TENAGA KERJA USAHA AYAM POTONG TERHADAP KESEJAHTERAAN MASYARAKAT DI KABUPATEN BIREUEN - Juniar Juniar; Khairil Anwar (LPPM Universitas Malikussaleh – Indonesia, 2020)
The purpose of this study is to look the effect of labor income of conducted in Bireuen District. The data used in this study are primary data sourced from 63 respondents. The data analysis method used in this study is a simple linear regression with the help of the eviews 10 program package. The results showed that the variable of labor income affects welfare and the magnitude of the effect of variable labor income on welfare by 0.0585 (5.85%). Recommendations, it is hoped that the local government will socialize the importance of the broiler business carried out in Bireuen Regency for the welfare of the community.